A compact planar dual band two‐port MIMO antenna with high isolation and efficiency. Issue 8 (14th May 2022) - Dong, Guiting; Huang, Jianlin; Chen, Zhizhou; Liu, Gui
Abstract: A dual‐band two‐port MIMO antenna with high isolation and efficiency is proposed in this article. Each antenna element is composed of a rotated U‐shaped strip and an L‐shaped strip. The MIMO antenna is optimized to operate in 2.5–2.7 GHz and 4.8–5 GHz, which can cover the 5G bands of China Mobile. The defected ground structure consists of a slant square loop with a T‐shaped slit and a U‐shaped slot. A rectangle parasitic strip is placed in the U‐shaped slot. The use of defected ground structure and parasitic strip makes the antenna obtain good isolation which is better than −17.96 dB and − 20.1 dB at the lower and higher frequency bands. To evaluate the antenna diversity, envelope correlation coefficient (ECC) is analyzed which is lower than 0.0006 and 0.12 at the lower and higher frequency bands, respectively. The measured gains are 4.35 dBi and 4.6 dBi, while the measured efficiencies are 63.23% and 68.69% at 2.6 GHz and 4.9 GHz, respectively. The prototype of antenna is fabricated to verify the functioning of proposed antenna design.